Perceptions of pancreatic surgeons and the current status of palliative care for pancreatic cancer in China: a multi-center online questionnaire survey - Qiaofei Liu; Yuze Hua; Jishu Wei; Qi Zhang; Zheng Wang; Xiaodong Tian; Feng Cao; Hanxiang Zhan; Song Gao; Shixiang Guo; Rongui Lin; Jinyong Xu; et al. (Journal of Pancreatology)
Objective:. To investigate the perceptions of pancreatic surgeons regarding palliative care for pancreatic cancer and the current status of palliative care for pancreatic cancer patients in China. Methods:. An online questionnaire consisting of 35 questions in 5 domains, including basic information of the respondents, personal interest, training and experiences of palliative care, recognition of the importance of palliative care, palliative care in the hospital of the respondents, and advice to improve the service of palliative care for pancreatic cancer, was distributed to pancreatic surgeons by the WeChat APP. All the data were automatically recorded and can be downloaded. The respondents’ perceptions of palliative care and the current status of palliative care were depicted, and the factors influencing the perceptions of the respondents and palliative care in hospitals were further analyzed. Results:. Responses from 429 pancreatic surgeons were validated. 81.4% were from tertiary hospitals, and 18.6% were from secondary hospitals. 94.2% were from general hospitals, and 5.8% were from cancer hospitals. Most surgeons have worked for over 5 years (93%), 72% had senior titles, and 54.5% held administrative positions. 49% have not read papers on palliative care before. 73.4% of the hospitals did not have a palliative care team, 77.9% did not have specific ward or bed for palliative care, 76.2% of the surgeons thought palliative care needed more attention in their hospitals. 97.4% of the surgeons thought palliative care was important for pancreatic cancer patients, and 94.9% were willing to join the palliative team. 46.6% of the surgeons thought palliative care should be conducted once pancreatic cancer was diagnosed. Most surgeons thought palliative care was helpful and should be involved in the multidisciplinary team. Regarding the geographical differences, surgeons and hospitals in North China performed better than in other regions. Surgeons with experience in clinical trials of pancreatic cancer performed better. The top 3 advice from the surgeons to promote palliative care were more education and training, seminars, and public broadcasting. 69.9% of the surgeons have concerns about the legal issue of implementation of palliative care. Conclusion:. In general, the majority of pancreatic surgeons in China lack training and experience in palliative care for pancreatic cancer, and the current status of palliative care in most hospitals needs to be further improved. Prevalence of the participants think that palliative care is very important for pancreatic cancer patients. Palliative care should be provided once pancreatic cancer is diagnosed, and palliative care should be involved in the multidisciplinary team. More seminars, education and training, and public broadcasting are practical ways to improve palliative care for pancreatic cancer patients.